CONTROL OF THE BUSINESS MANAGEMENT OF THE NATIONAL RURAL SANITATION PROGRAM FOR THE ECONOMIC DEVELOPMENT OF RURAL AREAS OF THE DEPARTMENT OF CAJAMARCA DURING THE YEAR 2020 (LACCEI, 2024)
Abstract: In an increasingly automated environment, where it is sought to manage processes more effectively, it was proposed to analyze the control of the business management of the National Rural Sanitation Program of the Ministry of Housing, Construction and Sanitation of Peru, which is in charge of to achieve the economic development of rural communes in the department of Cajamarca. The research is of a qualitative descriptive type, the study unit is the National Rural Sanitation Program, being the Peruvian state through its public powers who exercise supervision of the development of management. In the methodology, three methods were used: observation, documentary analysis and interview, to analyze the dimensions of business management through control in planning, organization and contractual execution, the objective of the research is to contribute through a proposal that covers the improvement of management control processes with an emphasis on the organization of the national rural sanitation program, based on the use of a table of needs, with a budgetary approach based on results, seeking to impact the achievement of the objectives of the institution analyzed to meet the needs of the population in rural areas of the department of Cajamarca.